The development and implementation of computer-based measurement system for energy band gap of semiconductor diode - Nor Shaida Mohd Saufi (Tanjong Malim, 2019)
The development and implementation of computer-based measurement system for energy band gap of semiconductor diode by Nor Shaida Mohd Saufi